Development Prospect of Reaping The Wood Industry In Pekanbaru - Wahyudi, Muhammad Roni; Putro, Tri Sukirno; ', Jahrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted in Pekanbaru, which aims to determine the effect of venture capital,labor, availability of raw materials and marketing efforts on the prospects of reaping the wood industry in Pekanbaru. The results of this study are expected to be useful to assist the company in developing a business and as an input in the making of policy.The population in this study is reaping wood industry in Pekanbaru, amounting to 51 reaping the wood industries. The technique of collecting data through questionnaires, interviews and observation methods. Analysis method using qualitative descriptive analysis.The survey results revealed that the factors affecting the development prospects of reaping thewood industry in Pekanbaru is the capital, labor and raw material availability. As for the marketing effort does not significantly affect the development prospects of reaping the wood industry in Pekanbaru. So it can be said to be reaping the wood industry prioritize these factors in making and developing businesses. In this case also required the participation of Pekanbaru Government in providing training for people who are not highly educated, especially in the field of reaping the wood and also oversees the industry that violates the rules, such as licensing issues get wood.